2016
DOI: 10.2217/fvl-2016-0093
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Latent Reservoir: Size Matters

Abstract: More than 35 million people remain infected with HIV-1. Upon antiretroviral therapy cessation, HIV-1-positive individuals systematically fail to achieve sustained virological remission, revealing the presence of a reservoir. This reservoir takes into account anatomical sanctuaries where HIV-1 continues to replicate, and latently infected cells also known as the latent reservoir (LR). A better understanding of the nature and features of the LR and its quantification are crucial to evaluate the efficiency of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 30 publications
(83 reference statements)
0
27
0
Order By: Relevance
“…Currently, there is no gold standard method to measure the size of HIV reservoir. 74,75 The quantitative viral outgrowth assay underestimates the size of HIV reservoir, [74][75][76] while the nucleic acid-based measures overestimate it, as only a portion of latently infected cells is able to reactivate and produce replicationcompetent virus. [77][78][79] However, recent reports indicated that levels of HIV DNA and RNA during ART are predictors of viral rebound upon therapy interruption.…”
Section: Levels Of Circulating Anti-inflammatory Glycans Associate Wimentioning
confidence: 99%
“…Currently, there is no gold standard method to measure the size of HIV reservoir. 74,75 The quantitative viral outgrowth assay underestimates the size of HIV reservoir, [74][75][76] while the nucleic acid-based measures overestimate it, as only a portion of latently infected cells is able to reactivate and produce replicationcompetent virus. [77][78][79] However, recent reports indicated that levels of HIV DNA and RNA during ART are predictors of viral rebound upon therapy interruption.…”
Section: Levels Of Circulating Anti-inflammatory Glycans Associate Wimentioning
confidence: 99%
“…Despite extensive studies in humans (5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), much remains unclear about HIV reservoirs that persist during ART (19)(20)(21)(22)(23). In part, this is because of technical limitations and limited access to appropriately collected tissues for such studies.…”
Section: Introductionmentioning
confidence: 99%
“…9 The viral reservoir is measurable through different methods, including viral outgrowth assay and intracellular HIV-1 DNA quantification. 10,11 Currently, there is no consensus on the best HIV-1 reservoir biomarker. Viral outgrowth assays only measure replication-competent proviruses and have therefore been considered to be the gold standard to measure the latent reservoir.…”
Section: Introductionmentioning
confidence: 99%